Investigating crack growth in two-dimensional plates with openings using the peri-dynamic method - Mohammad Norouzi Shavir; Pouria Biglari; Navid Mirzaii; Reza Rashmehkarim; Peyman Beiranvand (Sustainable Structures)
Analyzing and simulating the growth of dynamic cracks in the shell of structures and two-dimensional plates is one of the important topics for providing solutions to prevent crack growth and sudden failures, which increases the lifespan of the structure. Despite many studies by researchers regarding the behavior of structures against crack growth and sudden failure, there are still many problems regarding the analysis and simulation of the mechanical behavior of shells and plates with openings. Therefore, the peri-dynamic method can be directly used to model crack growth in these types of structures. In this research, modeling of dynamic crack growth as well as factors affecting crack growth and branching in the shell of structures (with and without openings) were investigated using the peri-dynamic method in LAMMPS software. Then the results obtained from the pre-dynamic method were verified with the results of other methods. The comparison of different results showed that the peri-dynamics method is capable of properly modeling crack growth in plates and shells with openings, and in other words, this theory can predict the path of crack growth with high accuracy. According to the obtained results, it can be stated that the process of crack growth and branching in the shell of structures depends on values such as the applied stress, the type of material and the direction of the fibers in the composites, as well as the absence of openings in the shell, which by changing these factors, the speed and The path of crack growth in the body of the structure changes.